The Influence Of Fintech User Experience, Fintech User Trust On Word Of Mouth By Using Fintech User Stickiness As Mediation - zuari, irsal; firmialy, sita deliyana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The swift and progressive technological progress in Indonesia has resulted in notable advancements, namely in the financial sector, with the rise of financial technology (fintech). The objective of this study is to examine how the user experience and trust in fintech services impact word-of-mouth recommendations, with user stickiness serving as a mediating element. The utilized research methodology is a quantitative approach. The researcher distributed a questionnaire to collect data, employing a Likert scale for measurement. The study's sample was selected from the community of digital wallet application users in Indonesia. The researcher managed to gather responses from 103 participants, and the data was analyzed using the SmartPLS application. The research findings suggest that Fintech User Experience does not exert a substantial influence on Fintech User Stickiness. Nevertheless, the impact of Fintech User Experience on Word of Mouth is substantial. User trust in fintech has an enormous effect on both user stickiness and word of mouth in the fintech industry. The characteristic of Fintech User Stickiness has a substantial influence on Word of Mouth. Fintech User Stickiness does not act as a mediating variable in the link between Fintech User Experience and Word of Mouth. In contrast, Fintech User Stickiness plays a crucial role in influencing the connection between Fintech User Trust and Word of Mouth.